3D Charge Transport Pathway in Organic Solar Cells via Incorporation of Discotic Liquid Crystal Columns. Issue 5 (6th May 2020) - Wang, Tong; Niu, Meng-Si; Guo, Jia-Jia; Zhang, Kang-Ning; Wen, Zhen-Chuan; Liu, Jian-Qiang; Qin, Chao-Chao; Hao, Xiao-Tao
Abstract : Discotic Liquid Crystals In article number 2000047, Jian‐Qiang Liu, Chao‐Chao Qin, Xiao‐Tao Hao, and co‐workers introduce 2, 3, 6, 7, 10, 11‐hexaacetoxytriphenylene (HATP) as an interlayer between poly(3, 4‐ethylenedioxythiophene): poly(styrene sulfonate) and the active layer in organic solar cells. This method achieves 3D charge transportation and higher mobility. Organic solar cells with HATP show weak triplet exciton generation and charge recombination. Thus, the short‐circuit current density and the resulting power conversion efficiency are increased.